Gene screening of colorectal cancers via network analysis - Mansouri, Vahid (Gastroenterol Hepatol Bed Bench, 2019)
AIM: Identifying crucial genes related to colorectal cancers via protein-protein interaction (PPI) network analysis is the aim of this study. BACKGROUND: colorectal cancer as major reason of mortality is evaluated by genetic and proteomic approaches to find suitable biomarkers. Chromosomal instability plays crucial role in CRC. Expression change of large numbers of genes is reported. METHODS: Differentially expressed genes related to CRCs which obtained from different proteomic methods were extracted from a review article of Paula Álvarez-Chaver et al. The genes interacted by Cytoscape software via STRING database. The central nodes determined and were enriched for biological terms by ClueGO. Action map for central genes was illustrated by CluePedia. The critical genes in CRC were introduced. RESULTS: Among 123 query genes, 114 one recognized by software and were included in the network. SRC, EGFR, PCNA, IL8, CTNNB1, TIMP1, CDH1, and HSPD1 were determined as central genes. After gene ontology analysis SRC, EGFR, and CDH1 were identified as critical genes related to CRC. CONCLUSION: It seems that SRC, EGFR, and CDH1 and the related pathways are possible biomarkers for CRC.